The influence of learning methods and students' learning interest on students' learning outcomes/students of santa maria junior high school year 2020/2021 (during the covid-19 pandemic) - nila sari rosenta sagala (Gladi : Jurnal Ilmu Keolahragaan, 2022)
This study aims to determine the effect of the independent variable on the dependent variable. Judging from the title of the thesis, there are two independent variables, namely online and conventional. The dependent variable is the physical education result of the Santa Maria Junior High School students. To determine the difference in the effect of online learning methods and conventional learning methods on physical education learning outcomes of Santa Maria Junior High School students, the interaction between online training methods and conventional learning methods on physical education learning outcomes of Santa Maria Junior High School students. This research was conducted at SANTA MARIA JUANDA JUNIOR HIGH SCHOOL, Central Jakarta. The research was conducted using an experimental method. Ex post facto research is research that aims to find the causes that allow changes in behavior, symptoms or phenomena caused by an event, behavior or things that cause changes in the independent variables which as a whole have occurred. Ex post facto research is methodologically an experimental research that also tests hypotheses but does not provide certain treatments for some reason it is unethical to provide treatment or provide manipulation. Usually for reasons of human ethics, or the symptoms/events have occurred and want to explore the factors that cause it or the things that influence it. The research method used to find the effect of a particular treatment or treatment. This study consisted of the dependent variable, namely the results of physical education learning outcomes, the independent variable being the treatment of online and conventional training methods and the moderator independent variable, namely the physical education learning outcomes of Santa Maria Junior High School students. There are differences in the learning outcomes of physical education skills in groups of students who have high interest who are taught by the face-to-face learning method who are taught by the overall learning method. It is known that Qcount 7.58 > 4.33 Qtable, so H0 is rejected, which means that there is a significant difference in physical skills learning outcomes between students who have high interest who are taught by the face-to-face learning method rather than those taught by the overall learning method. It is known that Qcount 0.85 < 4.33 Qtable means H0 accepted and H1 is rejected which means that there is no significant difference in physical skills learning outcomes in the group of students who have low interest who are taught by direct face-to-face learning methods and those taught by overall learning method. Based on this, it can be concluded that there is no significant difference in the learning outcomes of physical education skills in the group of students who have low interest between students who are taught using the face-to-face learning method and students who are taught by the overall learning method, although there are differences that indicate the average Physical education skills learning outcomes taught using online learning methods are better than students taught using face-to-face learning methods for students who have low interest.